SORPTIVITY AND CHLORIDE PENETRABILITY EVALUATION OF CONCRETE INCORPORATING FLY ASH AND SILICA FUME - Wahyuniarsih Sutrisno; Gabriel Ghewa; Priyo Suprobo (Journal of Civil Engineering, 2019)
Diffusion is believed to be the main mechanism of fluid ingress into the concrete. However, in partially saturated concrete, the fluid will mainly be absorbed by the capillary suction mechanism, which associates with the sorptivity properties of the concrete. This paper presents the results of an experimental program to investigate the influence of Portland cement substitution with Silica Fume (SF) and Type F Fly Ash (FA) on the rate of absorption, which also known as sorptivity, and chloride penetration of concrete. The sorptivity of the concrete was evaluated according to ASTM 1585, while the chloride penetration was evaluated according to ASTM C 1202. By substituting part of cement with FA and SF, it was found that the sorptivity of concrete is reduced. Furthermore, all type of concrete with supplementary material, including CFA, CSF and CSM, is confirmed to enhance the ability of concrete to resist chloride penetration compared yo normal concrete (NC).